TINJAUAN PSIKOLOGI PERKEMBANGAN TOKOH NOBUYUKI DI LINGKUNGAN PROSTITUSI YOSHIWARA DALAM CERPEN TAKEKURABEKARYA HIGUCHI ICHIYO - Sabrina, Tulus (Jurnal Ilmiah Mahasiswa FIB, 2013)
Short story is one of literary fiction exciting and in demand by today's society.Takekurabe short story can be analyzed through a variety of approaches one through the psychological approach, and this case the approach of developmentpsychology of Elizabeth B. Hurlock. This study answers the formulation of the problem, namely, howdevelopmentpsychology Nobuyuki character in Yoshiwara prostitution in the Takekurabe short story through the approach of development psychology of Elizabeth B. Hurlock. Analyzed from the development psychology of Elizabeth B. Hurlock’s theory, results of this study indicate that prostitution area factors have a strong current of the psychological development Nobuyuki figure, because of the strong influence of the environment can not figure Nobuyuki complete some developmental tasks in adolescence, in addition to the surrounding neighborhood character forming Nobuyuki. Nobuyuki be someone who has a psychiatric or psychological weak. Family environment are expected to provide a positive flow on psychological development Nobuyuki figures, was not able to give a positive flow or bring Nobuyuki figures on change for the better. For subsequent studies suggested toresearchthe inner conflict in the main character, or the emotional development character in Takekurabe short stories.   Keywords : Development psychology, developmental task, prostitution area effect